Establishing correlation between in vitro potency and in vivo immunogenicity for mRNA vaccines - Gautam Sanyal (npj Vaccines)
Abstract mRNA vaccines undergo intracellular translation to express the encoded protein antigen in a functionally intact form. To evaluate correlation between in vitro and in vivo measures of potency, mRNA vaccine samples with varying relative potencies can be created by gradual structural destabilization under stress including thermal stress. These samples can be tested in parallel for antigen expression in transfected cells and antigen-specific antibody induction and immune response in vaccinated animals.